1972
DOI: 10.1073/pnas.69.12.3602
|View full text |Cite
|
Sign up to set email alerts
|

Release of Polypeptide Chain Initiation Factor IF-2 During Initiation Complex Formation

Abstract: Polypeptide chain initiation factor IF-2 binds to 30S ribosomal subunits. This binding is enhanced by IF-2, one of the bacterial polypeptide chain initiation factors, is essential for the binding of both GTP and fMet-tRNA in a 30S initiation complex (1). This complex contains a 30S ribosomal subunit, mRNA, fMet-tRNA, and GTP (2,3). The combination of a 50S-subunit with the 30S complex results in the hydrolysis of GTP to GDP and Pi, concomitant with the formation of a functional 70S initiation complex (2,3). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…However, B. stearothermophilus IF2 can hydrolyze GTP in the absence of ribosomes when 20% ethanol is included in the reaction mixture (64). GTP hydrolysis in translation initiation has been suggested to be important for the release of IF2 from the 70S initiation complex (108,114), and for the adjustment of initiator tRNA in the ribosomal P-site (103). The crucial importance of GTP hydrolysis in translation initiation and its direct relation to cell viability have been confirmed by several studies of G-domain mutants of IF2 (98a, 100, 106, 115).…”
Section: Bacillus Subtilis Is the Only Organism That Does Not Belong mentioning
confidence: 59%
“…However, B. stearothermophilus IF2 can hydrolyze GTP in the absence of ribosomes when 20% ethanol is included in the reaction mixture (64). GTP hydrolysis in translation initiation has been suggested to be important for the release of IF2 from the 70S initiation complex (108,114), and for the adjustment of initiator tRNA in the ribosomal P-site (103). The crucial importance of GTP hydrolysis in translation initiation and its direct relation to cell viability have been confirmed by several studies of G-domain mutants of IF2 (98a, 100, 106, 115).…”
Section: Bacillus Subtilis Is the Only Organism That Does Not Belong mentioning
confidence: 59%
“…The hydrolysis of GTP coupled to fMet-tRNA binding is also markedly inhibited (4). In initiation reaction mixtures containing limiting levels of IF-2 with respect to ribosomes, maximum fMet-tRNA binding requires recycling of the factor (18,19,21). In contrast, when IF-2 is present in molar excess with respect to ribosomes, the catalytic role of IF-2 is unnecessary.…”
mentioning
confidence: 98%
“…IF-2 is released from the initiation complex and can recycle to catalyze another round of initiation (18)(19)(20).…”
mentioning
confidence: 99%
“…AcPhe-tRNAPhe and AcTyr-tRNATYr preparations also contained 35 and 30 x, respectively, of deacylated tRNAPhe and tRNATy'. However, the effects described cannot be attributed to these contaminants, since control experiments showed that the presence of 80 pmol deacylated tRNAPhe in the reaction mixture caused only a 12 "/o inhibition of AdoPhe-dependent GTPase and that lower concentrations [6], RNA phage replication [24] and possibly in the regulation of transcription [25]. Multifunctional proteins may contain autonomous structural regions (domains) that carry out the different functions [26].…”
Section: Effecl Of' N-blocked Acyluted Aminoucyl-trnamentioning
confidence: 99%
“…Howcver, at the molecular level very little is known of the interactions that trigger G T P hydrolysis. In the casc of elongation factor (EF) Tu, the reaction normally requires ribosomes, mRNA and aminoacyl-tRNA and is coupled to the binding to the ribosome of the aminoacyltRNA specified by the mRNA ( [ 6 ] , review). Our recent work, however, has shown that G T P hydrolysis can occur when only EF-Tu, ribosomes and 2'( 3')-O-~-phenylalanyladenosine (AdoPhe), i.e.…”
mentioning
confidence: 99%